Neogene fluvial systems in the Siwalik Group along the Tinau Khola section, west central Nepal Himalaya (Journal of Nepal Geological Society, 2001)
Along the Tinau Khola section of west central Nepal, the Siwalik Group is a 4 km thick pile of fluvial sedimentary sequence of mudstone, sandstone and conglomerate. It is exposed between the Main Boundary Thrust (MBT) to the north and the Frontal Churia Thrust (FCT), also known as the Main Frontal Thrust (MFT), in the south. The Siwalik Group is lithologically divided into the Arung Khola, Binai Khola and Chitwan formations, in ascending order. Six facies associations (FA1 to FA6) are recognised within the group based on grain size distribution, nature of bedforms, and sandstone-mudstone ratio. The fine-grained sediments of the Lower and Middle members of the Arung Khola Formation belong to the FA1-facies association and were interpreted to have deposited by a low-discharge, low -relief meandering fluvial system. The multiple accumulated thin-layered muddy sandstone sequence in the Upper Member of the Arung Khola and the Lower Member of the Binai Khola formations belong to FA2 and FA3- facies associations and were deposited by a flood flow-dominated meandering fluvial system. The deep sandy braided facies association (FA4) and shallow sandy braided facies association (FA5) are well developed in the Middle and Upper members of the Binai Khola Formation, respectively. The gravelly braided facies association (FA6) is recognised in the Chitwan Formation.The palaeomagnetically well-studied section of the Tinau Khola allows precise dating of the major change of fluvial system during the deposition of the Siwalk Group. The environment of predominantly shallow meandering rivers with low relief and low-discharge during the time of deposition of the Arung Khola Formation changed at 9.9 Ma and flooding in the rivers dramatically increased due to the intensification of monsoon precipitation. This hydrographic change also brought the change in facies from the earlier FA1 facies to FA2 and FA3 facies. Change from meandering to braided system occurred at 8.2 Ma because of the obvious regional tectonic upliftment of the Higher Himalaya bringing into FA4 and FA5-facies associations. Finally the FA6-facies association was developed due to the large gravelly braided system development at 2.5 Ma as a result of the Main Boundary Thrust movement along the frontal part of the Himalaya.